7(6-2a)=5(-3a+2)

Simple and best practice solution for 7(6-2a)=5(-3a+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(6-2a)=5(-3a+2) equation:


Simplifying
7(6 + -2a) = 5(-3a + 2)
(6 * 7 + -2a * 7) = 5(-3a + 2)
(42 + -14a) = 5(-3a + 2)

Reorder the terms:
42 + -14a = 5(2 + -3a)
42 + -14a = (2 * 5 + -3a * 5)
42 + -14a = (10 + -15a)

Solving
42 + -14a = 10 + -15a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '15a' to each side of the equation.
42 + -14a + 15a = 10 + -15a + 15a

Combine like terms: -14a + 15a = 1a
42 + 1a = 10 + -15a + 15a

Combine like terms: -15a + 15a = 0
42 + 1a = 10 + 0
42 + 1a = 10

Add '-42' to each side of the equation.
42 + -42 + 1a = 10 + -42

Combine like terms: 42 + -42 = 0
0 + 1a = 10 + -42
1a = 10 + -42

Combine like terms: 10 + -42 = -32
1a = -32

Divide each side by '1'.
a = -32

Simplifying
a = -32

See similar equations:

| 2y-5=3(3-r) | | 16x-16=16(4x-1) | | 4b-6-(b+2)= | | -60-7=67 | | 8y-6=4 | | 5(x+3)-4x=-3(x-5)+4x | | -60-7=-67 | | x-10x+3=-6-4x | | 8(n-4)+8n=-128 | | 12=-5p+8 | | 5s-s=332 | | 3x+2(x-20)=5(x-4) | | -60-7= | | 39.14+0.25x=130 | | 36x^4+5b^4x^2-b^8=0 | | 8(n+4)+8n=-128 | | 8r^2-200=8r^3-200r | | 64=8(r+t) | | -11v=-110 | | 1+5ln(12x)=0 | | 30000000+2x=8x | | 10 = 38(3x+16) | | 5s+s=332 | | 3(x+4)+2x=-3(x-4)+8x | | 4x+5=-4+2x+17 | | 5x+18-x=2(2x+18) | | -9(7k+8)=33-4k | | 5a+7=19+3a | | 4x+3=-5x-14 | | -7c=-11.7c-4.7 | | 7c+c=304 | | 8.7v-3.03+11.8v=19.5v-10.83 |

Equations solver categories